Judgment by Failure to Appear - Salma, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
The paper addresses the judgment by failure to appear, which was reintroduced by the new Law on Civil Procedure in 2011. An evolution of this type of judgment is shown, in particular the fact that the 2004 law abolished the judgment by failure to appear in general civil procedure, whereas the default judgement was introduced. In our new Law on Civil Action (ZPP), both institutes are kept. A common result - effect of these judgments is dealt with. Both failure of the defendant/respondent to appear and to file a pleading has as a consequence entering a judgment by which the claim of plaintiff is sustained. The paper analyses comparative legal solutions as well as the (evolution of) domestic theory and practice.